Dynamic hyperpolarized 13C MR spectroscopic imaging using SPICE in mouse kidney at 9.4 T. (19th December 2019) - Song, Jae Eun; Shin, Jaewook; Lee, Hansol; Choi, Young‐Suk; Song, Ho‐Taek; Kim, Dong‐Hyun
Abstract : This study aims to investigate the feasibility of dynamic hyperpolarized 13 C MR spectroscopic imaging (MRSI) using the SPectroscopic Imaging by exploiting spatiospectral CorrElation (SPICE) technique and an estimation of the spatially resolved conversion constant rate ( k pl ). An acquisition scheme comprising a single training dataset and several imaging datasets was proposed considering hyperpolarized 13 C circumstances. The feasibility and advantage of the scheme were investigated in two parts: (a) consistency of spectral basis over time and (b) accuracy of the estimated k pl . The simulations and in vivo experiments support accurate k pl estimation with consistent spectral bases. The proposed method was implemented in an enzyme phantom and via in vivo experiments. In the enzyme phantom experiments, spatially resolved homogeneous k pl maps were observed. In the in vivo experiments, normal diet (ND) mice and high‐fat diet (HFD) mice had k pl (s −1 ) values of medullar (ND: 0.0119 ± 0.0022, HFD: 0.0195 ± 0.0005) and cortical (ND: 0.0148 ±0.0023, HFD: 0.0224 ±0.0054) regions which were higher than vascular (ND: 0.0087 ±0.0013, HFD: 0.0132 ±0.0050) regions. In particular, the k pl value in the medullar region exhibited a significant difference between the two diet groups. In summary, the feasibility of using modified SPICE for dynamic hyperpolarized 13 C MRSI was demonstrated via simulations and in vivo experiments. The consistency of spectral bases over time and the accuracy of the estimated k pl values validate the proposed acquisition scheme, which comprises only a single training dataset. The proposed method improved the spatial resolution of dynamic hyperpolarized 13 C MRSI, which could be used for k pl estimation using high signal‐to‐noise ratio spectral bases. Abstract : A SPectroscopic Imaging by exploiting spatiospectral CorrElation (SPICE) technique was modified to acquire dynamic hyperpolarized 13 C MRSI. Based on the consistency of the spectral basis observed in simulation and in vivo experiments, the acquisition scheme was composed of a single FIDCSI and repeated EPSI. The proposed method improved the SNR of dynamic hyperpolarized 13 C MRSI and leads to the accurate estimation of k pl with high spatial resolution.